1000 CEOs - Davidson, Andrew, 1959- (DK Pub., 2009)
From humble beginnings to the stratospheric heights of corporate leadership, with all the progress and pitfalls on the way--learn how to succeed from one thousand of the world's most successful CEOs. For anyone interested in developing their business leadership skills, particularly those in middle management looking to progress in their career, this book is full of colorful and instructive career anecdotes and advice from business leaders around the globe.--From publisher description.